Handling of Narcotics Child Victims in Child Special Coaching Institutions Class I Tanjung Gusta, Medan - Friska Tumanggor; Muazzul Muazzul; Rizkan Zulyadi (Budapest International Research and Critics University, 2019)
Handling of Narcotics Child Victims in Child Special Coaching Institutions Class I Tanjung Gusta, Medan based on Law No. 23 of 2002 concerning Child Protection which is to provide supervision, direct for worship, equip in the field of formal education and skills training, and provide adequate facilities to children who commit narcotics crime. That is a way to make a criminal child free from narcotics goods, so that when a child who commits a narcotics crime out of a development institution has the skills and soul to re-socialize with the community. The problems discussed in this study are how the legal rules governing the handling of child victims of narcotic crime in prison in dealing with narcotics crime committed by children of Tanjung Gusta Medan and How are the factors causing the occurrence of narcotics abuse committed by children of Tanjung Gusta Medan, as well as how the efforts to tackle the crime of drug abuse committed by children of Tanjung Gusta Medan. The method used in this writing is empirical juridical namely reviewing the applicable legal provisions and what happens in the reality of society. The data collection techniques are carried out through library research (liberary research) and also field research (field research), namely by conducting direct interviews of studies at the Penitentiary Special Class I Tanjung Gusta Medan.